Proceedings of the 2007 InSITE Conference 2007
DOI: 10.28945/3122
|View full text |Cite
|
Sign up to set email alerts
|

Using an Outcome-Based Information Technology Curriculum and an E-Learning Platform to Facilitate Student Learning

Abstract: A recently established university in the United Arab Emirates has shifted from an input-based teaching model to an outcome-based learning model. The outcome based academic model is new in the Gulf region and is designed to allow students and faculty members to work together to foster learning. This model is a dramatic departure from the traditional input model where students in the Gulf have learned to mainly accept and retain information. Using the university's learning outcomes model, the College of Informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…ERMS is seen as a set of processes that are instrumental in improving HPE effectiveness. Prior studies in this area have revealed several barriers that developing nations face when adopting ERMS (e.g., [16], [32], [33]).…”
Section: The Need For Higher Professional Educational Institutions To Adopt Electronic Records Management Systemsmentioning
confidence: 99%
“…ERMS is seen as a set of processes that are instrumental in improving HPE effectiveness. Prior studies in this area have revealed several barriers that developing nations face when adopting ERMS (e.g., [16], [32], [33]).…”
Section: The Need For Higher Professional Educational Institutions To Adopt Electronic Records Management Systemsmentioning
confidence: 99%
“…But this content is not interactive nor assists learning programming languages [4]. The learners who are new to technical education or engineering graduation will have very less knowledge about computers and programming languages [4]. So if the lecturers try to load the new paradigms or concepts with the traditional teaching methods and techniques the learners' fail to grasp the new concepts.…”
Section: B Computer and Web Based Teachingmentioning
confidence: 97%
“…This may be useful for distance learners who are unable to attend classes [3]. But this content is not interactive nor assists learning programming languages [4]. The learners who are new to technical education or engineering graduation will have very less knowledge about computers and programming languages [4].…”
Section: B Computer and Web Based Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…ICT is seen as a set of processes that are instrumental in improving educational institutions' effectiveness. Prior studies in this area have revealed several barriers that developing nations face when adopting ICT such as EMRS [39,67,68,69]. Recent research has shown that ICT adoption, particularly e-learning systems adoption, is still early [40,41,46,70].…”
Section: Background and Related Workmentioning
confidence: 99%